Impacto tecnológico de la modalidad de estudio híbrida a “distancia-virtual-semipresencial” caso carrera de Ingeniería Ambiental - Delgado Tuárez, Josselyn Emilia (2023)
The hybrid teaching modality is receiving more and more attention in the field of education. The objective of this research was to determine the technological impact of the hybrid distance-virtual-blended study modality on the learning of students of the Environmental Engineering career at ESPAM MFL to guarantee the right to higher education. The methodology used was based on a type of documentary descriptive research, in the same way the methods were the inductive, deductive and synthetic analytical method. In addition, collection techniques were used such as: the survey and the interview, necessary to obtain data, with which the background and legal framework of the local panorama of the technological impact of the modality under study were analyzed, likewise, the diagnosis in the learning of the students of the environmental engineering career and with the results obtained, propose an action plan that allows the academic mitigation of the students of the environmental engineering career in the study modality. It is concluded that in terms of the change of study modality, adaptation was difficult, both for teachers and students, likewise, in 51.6% of the respondents it is established that there are affectations, because they do not perceive that they are learning correctly with this modality. For what was recommended, that it is necessary that within the institution they have an action plan regarding the implementation of new study modalities, that is, contribute new long-term strategies.